Extraction and physicochemical analysis of some selected seed oils - Afolayan, Michael; Fausat, Akanji; Idowu, Doyinsola (International Journal of Advanced Chemistry, 2014)
Oil was extracted from the seeds of groundnut, melon and Moringa oleifera. The physicochemical properties of groundnut oil, melon oil and moringa oil were determined. The acid value obtained was 9.76 mgKOH/g, 7.85 mgKOH/g and 1.91 mgKOH/g for moringa, melon and groundnut oil respectively. The Iodine value was found to be 35.85 mg/g, 83.75 mg/g and 59.64 mg/g for moringa, melon and groundnut oil respectively. The Peroxide values were moringa oil - 13.80 meq/kg, melon oil - 5.60 meq/kg and groundnut oil - 10.80 meq/kg. Unsaponifiable matter values were moringa oil - 8.59 g/kg, melon oil - 2.18 g/kg, groundnut oil - 5.77 g/kg while the saponification values were moringa oil - 155.68 mgKOH/g, melon oil - 180.92 mgKOH/g and groundnut oil - 168.30 mgKOH/g. The volatile matter in the oils was found to be 0.06. 0.07 And 0.04 in groundnut, melon and moringa oil respectively. All the oils were pale yellow in colour and liquids at room temperature. The results obtained from the physicochemical characterization of the oils shows that moringa oleifera seed oil compares favourably with the other oils and has high potentials for use both as domestic oil and as industrial oil. Keywords: Groundnut, Melon, Moringa Oleifera, Oil, Physicochemical.